PERLINDUNGAN HUKUM TERHADAP JUSTICE COLLABORATOR PADA TINDAK PIDANA PEMBUNUHAN BERENCANA: Legal Protection of Justice Collaborator in The Crime of Premeditated - Grace Angelia Purba; Tawang, Dian Adriawan Daeng (Faculty of Law, Universitas Trisakti, 2025)
Premeditated murder is a serious crime faced by the Indonesian legal system, often putting pressure on witnesses, especially justice collaborators. The research question in this study is how justice collaborators are legally protected in cases of premeditated murder, with reference to the Witness and Victim Protection Law and SEMA Number 4 of 2011. This study employs a normative-descriptive approach with an analysis of Judgment No. 79/Pid.B/2024/PN Sng. The data sources used are secondary data, with primary and secondary legal materials analyzed qualitatively. The results and conclusion of the study indicate that although premeditated murder is not explicitly mentioned in the UUPSK and SEMA as a specific criminal offense eligible for justice collaborator status, Danu is entitled to protection due to his role in revealing important facts and the serious threat to his safety.